Recent progress in electrochemical reduction of carbon monoxide toward multi-carbon products. (October 2022) - Du, Huitong; Fu, Jiaju; Liu, Li-Xia; Ding, Shichao; Lyu, Zhaoyuan; Chang, Yu-Chung; Jin, Xin; Kengara, Fredrick O.; Song, Bing; Min, Qianhao; Zhu, Jun-Jie; Du, Dan; et al.
Graphical abstract: Abstract: The increasing CO2 emissions and accompanying climate challenges have boosted the exploration of candidate pathways for storing and utilizing renewable carbon resources. Electrochemical CO2 reduction (ECO2 R) has been proven as a promising technology for artificial carbon fixation. Nevertheless, the unsatisfactory multi-carbon (C2+ ) product selectivity hinders its widespread use. Recently, the indirect route via electrochemical CO reduction (ECOR) to C2+ products has become a potential alternative through the combination with ECO2 R. In this review, we briefly summarize the most recent and instructive research in the ECOR development process from advanced ECOR catalysts and reaction mechanisms. Furthermore, the challenges and outlooks based on current understanding in this field are expounded. These insights and perspectives offer meaningful guidance for grasping ECOR and designing relevant catalysts with enhanced C2+ product selectivity.